Reflections on Education and Gender - Ileana Vargas-Jiménez (Universidad Nacional, Costa Rica, 2011)
This paper provides an analysis on how education, since the first grades and based on the official or a hidden curriculum, favors several elements that tend to create differences in terms of gender. The study presents different aspects, such as television programs and some teaching practices, that have a direct effect on gender discrimination. There are also recommendations on how to counteract gender discrimination, and conclusions are provided in the last section.